1991
DOI: 10.1111/j.1524-4725.1991.tb03425.x
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence Rates of Treated Basal Cell Carcinomas: Part 2: Curettage‐Electrodesiccation

Abstract: This is the second article in a series that reviews the experience in the Skin and Cancer Unit, from 1955 through 1982, with the treatment of basal cell carcinomas (BCCs). This report deals with 2314 previously untreated (primary) BCCs removed by curettage-electrodesiccation. Multivariate analysis showed that increasing lesion diameter (P less than .001), high-risk anatomic sites (nose, paranasal, nasal-labial groove, ear, chin, mandibular, peri-oral, and peri-ocular areas) (P less than .001), middle-risk anat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
150
5
4

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 210 publications
(170 citation statements)
references
References 25 publications
(31 reference statements)
11
150
5
4
Order By: Relevance
“…On the basis of the best available literature, the most useful stratification of BCC is provided by the National Comprehensive Cancer Network (NCCN) Guidelines (for recommendation, see Table II; for level of evidence/strength of recommendation, see Table III). 2,3,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] The NCCN stratification, listed in Table IV, takes both clinical and pathologic parameters into account and is based on a combination of available evidence and expert multidisciplinary opinion, including representatives from dermatology, dermatopathology, head and neck surgery, plastic surgery, and surgical, radiation, and medical oncology. Treatment recommendations throughout the current guidelines are based on this stratification.…”
Section: Grading and Stagingmentioning
confidence: 99%
See 2 more Smart Citations
“…On the basis of the best available literature, the most useful stratification of BCC is provided by the National Comprehensive Cancer Network (NCCN) Guidelines (for recommendation, see Table II; for level of evidence/strength of recommendation, see Table III). 2,3,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] The NCCN stratification, listed in Table IV, takes both clinical and pathologic parameters into account and is based on a combination of available evidence and expert multidisciplinary opinion, including representatives from dermatology, dermatopathology, head and neck surgery, plastic surgery, and surgical, radiation, and medical oncology. Treatment recommendations throughout the current guidelines are based on this stratification.…”
Section: Grading and Stagingmentioning
confidence: 99%
“…When the clinician is submitting biopsy tissue for histopathologic diagnosis, the work group recommends that whenever possible and appropriate, key elements of patient demographics, clinical presentation, and clinical history should be provided to the pathologist (see Table VI; for level of evidence/ strength of recommendations, see Table III). These include patient age and biologic sex, [17][18][19][20][21][22][23][24][25] anatomic location, [17][18][19][20][22][23][24][25][26] and any history of treatment at the same anatomic site. 17,18,22,23 Additional desirable relevant information includes the clinical size of the lesion 17,18,[20][21][22][23][24][25][26] and whether the patient currently, or previously encountered additional risk factors, such as immunosuppression, radiation treatment, or solid organ transplantation.…”
Section: Clinical and Pathologic Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recurrence rates are varied between 3% to 19%im 5 years (78). Recurrence was higher in nasal, paranasal, and forehead areas (78). Although ED & C appears to have a higher risk for disease recurrence compared with surgical excision, a nonrandomized retrospective chart review suggested that the two treatment modalities are not significantly different (79).…”
Section: Curettage and Electrodesiccationmentioning
confidence: 99%
“…Typically two or three treatment cycles are recommended to completely remove the tumor (77). Recurrence rates are varied between 3% to 19%im 5 years (78). Recurrence was higher in nasal, paranasal, and forehead areas (78).…”
Section: Curettage and Electrodesiccationmentioning
confidence: 99%